2022
DOI: 10.3389/fvets.2022.846298
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Pathogenicity Analysis of the Pathogen Causing Spotted Spleen in Muscovy Duck

Abstract: Since September 2020, the clinical symptoms of Muscovy duck spleen spots have appeared in Guangdong, Guangxi, Jiangxi, Hunan, Hubei, and other provinces, resulting in a large number of Muscovy duck deaths and great economic losses. The absence of the typical clinical symptoms caused by pathogenic microorganisms makes the cause of the spotted spleen a mystery. High-throughput sequencing results suggested that Riemerella anatipestifer (R. anatipestifer) may be the pathogen. Then, R. anatipestifer was regarded as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…RA infection can cause gross lesions and a spotted spleen with mild pericarditis, liver capsule hepatorrhagia, and cerebral hemorrhage in Muscovy ducks. The infected ducks histo-pathologically develop extensive white myeloid fibrinoid necrosis with a marked loss of cell structure or residual necrotic fragmented nuclei, an unclear boundary between red and white pulp, more diffuse white pulp, and no obvious inflammatory infiltrates in the spleen [9]. Our study showed similar findings, suggesting that RA infection impairs and disorganizes the spleen compartments, affecting the immunological function of the spleen because it is the site of homing and differentiation of immune cells (i.e., macrophages, monocytes, granulocytes, dendritic cells, and plasma cells) [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RA infection can cause gross lesions and a spotted spleen with mild pericarditis, liver capsule hepatorrhagia, and cerebral hemorrhage in Muscovy ducks. The infected ducks histo-pathologically develop extensive white myeloid fibrinoid necrosis with a marked loss of cell structure or residual necrotic fragmented nuclei, an unclear boundary between red and white pulp, more diffuse white pulp, and no obvious inflammatory infiltrates in the spleen [9]. Our study showed similar findings, suggesting that RA infection impairs and disorganizes the spleen compartments, affecting the immunological function of the spleen because it is the site of homing and differentiation of immune cells (i.e., macrophages, monocytes, granulocytes, dendritic cells, and plasma cells) [29].…”
Section: Discussionmentioning
confidence: 99%
“…RA infection can be acute or chronic, with acute infection being more common in ducks younger than 8 weeks of age [7]. Infection is often referred to as new duck disease, riemerellosis, infectious serositis, or duck septicemia, and clinical characteristics include diarrhea, lethargy, ocular and nasal discharge, respiratory symptoms (i.e., dyspnea, mild coughing and sneezing), and nervous symptoms (i.e., tremors of the head and neck or head and legs and ataxia) in addition to pathologic lesions such as fibrinous pericarditis, perihepatitis, airsacculitis, and meningitis [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It incurs high morbidity and mortality rates among waterfowl, resulting in substantial economic losses for the poultry industry across various countries and regions (Tao et al, 2020). R. anatipestifer has numerous serotypes (Ke et al, 2022). Given that no cross immunoprotective effect occurs among these serotypes, vaccine development and disease control for R. anatipestifer infections remains challenging (Chu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%